Ageing of a polymeric engine mount investigated using digital image correlation. (October 2018) - Tang, Ning; Soltani, Payam; Pinna, Christophe; Wagg, David; Whear, Roly
Abstract: Polymeric engine mounts have been widely used as vibration isolators in vehicles. In general, understanding ageing-dependent stiffness is important for life cycle design. In this paper, a new experimental procedure is developed to study the ageing mechanisms of service-aged engine mounts using digital image correlation measurements. The present contribution demonstrates that the leading factors for ageing-dependent stiffness are, not only the elastic modulus variation, but also the creep deformation and micro-structural change. The results show that pure thermal effects, such as that used to simulate ageing, leads to a uniform change in the rubber component inside the mount. This is not the same as the service-aged mount behaviour. In addition, the cross-sectional creep deformation dominates the increase in rigidity. Finally, the results suggest that micro-structural change may also lead to the stiffness variation of the mounts with high working mileage. Highlights: A novel experimental procedure has been developed to study engine mount ageing mechanisms. Material ageing is uniform and homogeneous when an engine mount is only exposed to high thermal loads. Non-uniform ageing for the service-aged mounts may be partly caused by the development of additional contacts. A combined effect of creep deformation and internal micro-structural changes may be the reason for the softening behaviour. The classic thermal accelerated ageing tests fail in simulating the stiffness variation of a service-aged engine mount.